2021
DOI: 10.1024/1661-8157/a003661
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 und Kopfschmerzen

Abstract: Zusammenfassung. Kopfschmerzen sind ein häufiges Symptom einer COVID-19-Infektion und werden typischerweise als bilateral lokalisiert, frontal betont, drückend und mittelstark bis stark beschrieben. Die Unterscheidung von primären Kopfschmerzerkrankungen gelingt in der Regel durch die systematische Suche nach «Red Flags»; meist werden die Kopfschmerzen von Fieber, Husten oder erhöhten Entzündungsparametern im Blut begleitet. Früher geäusserte Bedenken gegen den Einsatz von Ibuprofen zur symptomatischen Kopfsch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
1
0
0
Order By: Relevance
“…Our results were similar to the findings of a prospective study of nearly 900 patients with SARS-Cov-2 infection where the presence of headache was a protective factor against death due to COVID-19 [7]. The frequency of headache in previous studies has been reported as between 7% and 75%, with higher percentages in European populations than in Chinese cohorts [11].…”
Section: Discussionsupporting
confidence: 91%
“…Our results were similar to the findings of a prospective study of nearly 900 patients with SARS-Cov-2 infection where the presence of headache was a protective factor against death due to COVID-19 [7]. The frequency of headache in previous studies has been reported as between 7% and 75%, with higher percentages in European populations than in Chinese cohorts [11].…”
Section: Discussionsupporting
confidence: 91%